Street triage services in England: service models, national provision and the opinions of police. (17th September 2018) - Kirubarajan, Abirami; Puntis, Stephen; Perfect, Devon; Tarbit, Marc; Buckman, Mary; Molodynski, Andrew
Abstract : Aims and method: Street triage services are increasingly common and part of standard responses to mental health crises in the community, but little is understood about them. We conducted a national survey of mental health trusts to gather detailed information regarding street triage services alongside a survey of Thames Valley police officers to ascertain their views and experiences. Results: Triage services are available in most areas of the country and are growing in scope. There is wide variation in levels of funding and modes of operation, including hours covered. Police officers from our survey overwhelmingly support such services and would like to see them expanded. Clinical implications: Mental health crises now form a core part of policing and there are compelling reasons for the support of specialist services. Recent changes to the law have heightened this need, with a requirement for specialist input before a Section 136 is enacted. Those who have experienced triage services report it as less stigmatising and traumatic than a traditional approach, but there remains little evidence on which to base decisions. Declaration of interest: None.